Mediating role of strategic orientations in the relationship between entrepreneurial orientation and performance of Saudi SMEs - Abdulrab, Mohammed; Al-Mamary, Yaser Hasan Salem; Alwaheeb, Mohammed A.; Alshammari, Naif Ghazi M.; Balhareth, Hamad; Al-Shammari, Serhan A. (Brazilian Journal of Operations & Production Management, 2021)
Goal: This study aims to examine the mediating role of strategic orientations in the relationship between entrepreneurial orientation and performance of small and medium enterprises (SMEs) in Saudi Arabia. Design/Methodology/Approach: Quantitative analysis techniques is used in this study. Data from 206 KSA owners / managers of SMEs is obtained and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). Results: Findings indicate that strategic orientations mediate the relationship between entrepreneurial orientation and performance of SMEs in Saudi Arabia. Limitations of the investigation: The proposed model may not be generalised and must be applied in other contexts and cultures. Practical implications: This study indicates that KSA managers should maintain emphasis on entrepreneurship and establish unique strategic techniques to improve efficiency. Policymakers are recommended to establish entrepreneurship initiatives for SMEs to form entrepreneurship. Additional recommendations are also provided. Originality / Value: This study adds to the current body of knowledge by addressing the mediating role of market and technology orientation in the relationship between entrepreneurial orientation and performance of Saudi SMEs.